(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on the publications made in high impact journals indexed in Scopus database regarding the implementation of policies for Educational Inclusion in Latin America during the period between 2015 and 2020. The information was identified through the application of search filters in the aforementioned platform, and organized by means of tables and figures that allow the realization of a quantitative analysis of the information where main characteristics such as year of publication, country of origin, area of knowledge and type of publication are mentioned. The total number of publications is 986 documents, Brazil is identified as the Latin American country with the highest number of publications, a total of 482 documents, and the year with the highest number of publications in the period was 2020, when 245 research works were registered. The area with the highest number of contributions to the execution of research projects related to the topic under study was Social Sciences with a total of 554 documents and the type of publication chosen by most authors was the journal paper, which represents 76% of the total production. Similarly, examples of publications are identified to establish the position of the main authors regarding the management of policies to implement inclusive inclusion strategies in Latin American academic institutions.